Pendekatan Modular Pada Interior Rental Office Di Denpasar - Giri, Kadek Risna Puspita; Utami, Ni Kadek Yuni; Trisna, Ni Made Sri Wahyuni; Molo, Bethovent (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
As development progresses, urban land is becoming increasingly scarce. From these problems, land prices in areas that are considered strategic have increased. One of them is Denpasar City, which is experiencing an increase in population due to urbanization and an increase in the economic sector, resulting in high occupancy demand for office facilities, but cannot be fulfilled due to several factors and the concept of the available offices is still conventional. Meanwhile, office activities today tend to be dynamic and do not require extensive office facilities. Through the design of Rental Office in Denpasar with a modular concept, flexible office needs can be met. The application of the space module system will facilitate the optimization of space that can be adjusted according to the activity needs of users, and is equipped with shared facilities. The method used is the programmatic method, which determines a theme and concept from the existing problems and how to solve the problem itself, resulting in the theme and concept of industrial-modular. The expected result with the presence of this design is that it can help entrepreneurs who want to have an office with affordable rent. For a greater impact, it is expected to trigger a trend of entrepreneurship for the younger generation so that it affects the increase in the people's economy.